The Extent of Primary School Mathematics Teachers’ Knowledge of Constructivist Teaching Skills from Their Perspectives - Noor Ali Abdul Karim; Anwar Sabah Abdul-Majid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The present study aims to identify the level of primary school mathematics teachers’ knowledge of constructivist teaching skills from their own perspectives. To achieve the objective of the study, the researchers adopted the descriptive-analytical approach, as it is appropriate for the nature and aims of the research. The study sample consisted of 360 male and female mathematics teachers, representing 30%of the total population.The research instrument was a questionnaire consisting 52 items distributed across four domains: planning learners’ prior knowledge, teaching and learning activities, classroom environment, and assessment. The instrument was reviewed by a panel of experts to ensure its validity before being administered to a pilot sample, through which  validity, reliability, and item analysis were established.Subsequently, the questionnaire was administered to the main study sample, and the data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results revealed that primary school mathematics teachers possessed constructivist teaching skills at a moderate degree.In light of these findings, the researchers recommend training mathematics teachers on the effective implementation of constructivist theory in teaching through the development of training programs based on constructivist thinking, as well as providing a classroom environment that facilitates the application of these skills. Furthermore, the researchers suggest conducting similar studies to explore the use of constructivist teaching skills in other educational stages and subject areas.DOI: https://doi.org/10.54633/2333-025-058-011